NLFEA Behavior of Heat-Damaged Key Joints in Precast Concrete Segmental Bridge - Bara’a R. Alnemrawi; Rajai Al-Rousan (Buildings)
The provided shear key joints are practically unreinforced due to their small size, and their performance directly affects the structural behavior of the segmental concrete bridge. In addition, these joints are usually dry and distributed over the contact region between the two connected bridge parts. The current research examines the effect of the lateral confinement pressure (1, 2, 3, 4, 5, and 6) MPa and the elevated temperature values (23, 200, 400, and 600) °C on the behavior of single dried shear key joints structural behavior tested under concentrated static loading using the Nonlinear Finite Element Analysis (NLFEA) procedure. The simulation models were first validated using experimental data from the literature and compared using the ultimate deflection, ultimate load, cracking propagation, and failure modes using ABAQUS software, where the available Concrete Damage Plasticity model was utilized. Twenty-four models were simulated using different combinations of the parameters included in the parametric study. Results were reported in terms of their load-deflection behavior, structural characteristics, cracking propagation within the shear key zone, and the final failure modes. It has been found that the initial stiffness, ultimate deflection, and ultimate strength values were all increased under increasing confinement pressure. Moreover, the situation is totally different when the exposure temperature exceeds 400 °C. Finally, a new formula was introduced for predicting the shear key capacity after being validated against numerical and experimental data sets, along with different design codes and standards. A very good agreement was reached for the new proposed mathematical equations.